DECISION SUPPORT SYSTEM TO CHOOSE DIGITAL SINGLE LENS CAMERA WITH SIMPLE ADDITIVE WEIGHTING METHOD - Putri, Tri Pina; Rosa, Paulina H. Prima (Scientific Journal of Informatics, 2016)
One of the technologies that evolve today is Digital Single Lens Reflex (DSLR) camera. The number of products makes users have difficulties to choose the appropriate camera based on their criteria. Users may utilize several ways to help them choosing the intended camera such as using magazine, internet, and other media. This paper discusses about a web based decision support system to choose cameras by using SAW (Simple Additive Weighting) method in order to make the decision process more effective and efficient. This system is expected to give recommendations about the camera which is appropriate with the users need and criteria based on the cost, the resolution, the feature, the ISO, and the censor. The system was implemented by using PHP and MySQL. Based on the result of questionnaire distributed to 20 respondents, 60% respondents agree that this decision support system can help users to choose the appropriate camera DSLR in accordance with the users need, 60% of respondents agree that this decision support system is more effective to choose DSLR camera and 75% of respondents agree that this system is more efficient. In addition, 60.55% of respondents agree that this system has met 5 Es Usability Framework.